2014
DOI: 10.3109/00365513.2014.921931
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic tube-transported blood samples in lithium heparinate gel separator tubes may be more susceptible to haemolysis than blood samples in serum tubes

Abstract: Pneumatic tube systems are widely used in hospitals. Advantages are high speed and rapid availability of the samples. However, the transportation by pneumatic tube promotes haemolysis. Haemolysis interferes with many spectrophotometric assays and is a common problem in clinical laboratories. The haemolysis index (HI) as a semi-quantitative representation of the level of haemolysis was compared in unpaired tube-transported and hand-delivered routine lithium heparinate plasma samples (n = 1368 and n = 837, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…This study is the first to demonstrate that RST tubes can significantly reduce PTS-induced haemolysis, resulting in fewer haemolysis-related sample rejections. Our findings are consistent with previous studies who found PTS transport of clotted blood maintains sample integrity better than anticoagulated blood 2–4. Our study sheds additional light on the mechanism of protection offered by clotted blood through the use of RST that ensures the sample is completely clotted before transport.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study is the first to demonstrate that RST tubes can significantly reduce PTS-induced haemolysis, resulting in fewer haemolysis-related sample rejections. Our findings are consistent with previous studies who found PTS transport of clotted blood maintains sample integrity better than anticoagulated blood 2–4. Our study sheds additional light on the mechanism of protection offered by clotted blood through the use of RST that ensures the sample is completely clotted before transport.…”
Section: Discussionsupporting
confidence: 92%
“…Susceptibility to PTS-induced haemolysis varies among blood collection tube type, suggesting another mitigation strategy laboratories can easily implement. A higher rate of PTS-induced haemolysis has been observed in lithium heparin tubes relative to serum tubes, leading to the speculation that cells within a clot are protected from the mechanical stresses of PTS transport 2 3. Additionally, air bubble formation during PTS transport of anticoagulated blood has been shown to contribute to haemolysis 4.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the RCV , the decrease in PHOS concentration after 3–4 hr of whole blood storage and the slight decreases observed for LDH and K concentrations can be considered devoid of clinical significance up to 6 hr (RCV = 23.1%, 24.4%, and 13.4%, respectively; Supporting Information Table B), as previously reported . Finally, it must be noted that the design of our substudy on whole blood did not take into account the influence of the pneumatic tube system, which potentially increases the hemolysis degree, thus impacting the concentration of sensitive analytes .…”
Section: Discussionmentioning
confidence: 77%
“…Several papers describe how PTS may increase the risk of in vitro hemolysis [2,[8][9][10]. Clinical chemistry analyses are most often discussed in this context; however, blood gas, hematology and coagulation analyses have also been subject to evaluation when assessing the effects of PTS on specimen integrity [4,11,12].…”
Section: Introductionmentioning
confidence: 99%